Quantum information approach to the azurite mineral frustrated quantum magnet - Batle, J.; Raymond Ooi, C.H.; Abutalib, M.; Farouk, A.; Abdalla, S. (Springer Verlag (Germany), 2016)
Quantum correlations are almost impossible to address in bulk systems. Quantum measures extended only to a few number of parties can be discussed in practice. In the present work, we study nonlocality for a cluster of spins belonging to a mineral whose structure is that of a quantum magnet. We reproduce at a much smaller scale the experimental outcomes, and then, we study the role of quantum correlations there. A macroscopic entanglement witness has been introduced in order to reveal nonlocal quantum correlations between individual constituents of the azurite mineral at nonzero temperatures. The critical point beyond which entanglement is zero is found at Tc<1K.